Production process of fly ash type steam-cured ceramsite
By using raw materials such as fly ash, silica fume, diatomaceous earth, etc., combined with pore-generating agent and fast-coagulant, high-strength, low-expanding fly ash-type steamed clay granules are prepared using steaming and curing technology, which solves the problems of high energy consumption, high cost and poor performance of burn-free clay granules in the existing clay preparation process, and achieves low-cost and efficient clay preparation.
Patent Information
- Application Number
- CN202411931110.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-18
AI Technical Summary
The existing ceramic preparation process has the problems of high energy consumption, high cost, and the strength and expansion coefficient of the sintered ceramic particles are inferior to those of sintered ceramic particles.
High-strength, low-expansion fly ash-type steamed-cultivating ceramic granules are prepared through steaming and curing process by using raw materials such as fly ash, silica fume, diatomaceous earth, combined with pore-generating agent and fast-coagulant agent.
It significantly reduces production costs and energy consumption, and the prepared ceramic cylinder has high pressure strength, excellent durability, and does not require high-temperature firing, which meets environmental protection requirements.
Smart Images

Figure BDA0005211224910000061 
Figure BDA0005211224910000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of comprehensive utilization of industrial waste resources, and specifically relates to a production process of fly ash type steam-cured ceramsite. Background Art
[0002] Fly ash is the main solid waste in the coal-fired power industry. The preparation of ceramsite from fly ash is one of the important ways to utilize fly ash resources. Fly ash is the residual product after coal combustion. It is the main solid waste in the coal-fired power industry and one of the industrial solid wastes with the largest emission in my country. It is produced by various inorganic and organic components in the raw coal. The main components include SiO2, Al2O3, FeO, Fe2O3, CaO and TiO2. Large amounts of fly ash are stored, occupying precious land resources. After long-term weathering and leaching by precipitation, toxic and harmful substances in fly ash will penetrate into the ground, pollute the soil and groundwater, and seriously endanger the environment on which human beings depend for survival. Therefore, it is of great significance to increase the comprehensive utilization of fly ash and promote the resource utilization of solid waste. At present, the main utilization of fly ash includes cement, concrete and building materials production.
[0003] Expanded clay is a man-made lightweight aggregate with high strength, low density, large specific surface area, high porosity, strong adsorption and pollution interception ability, good thermal stability, corrosion resistance, water-proof and air-retaining, as well as thermal insulation. Therefore, it is widely used in construction projects, landscaping, sewage treatment and other fields.
[0004] The preparation of ceramsite using fly ash as raw material can effectively realize the recycling of solid waste and obtain value-added products. The preparation process of fly ash ceramsite can be divided into sintering method and non-fired method. Among them, the sintering method for preparing fly ash ceramsite is mature, the product has high strength and low bulk density, but it has disadvantages such as high energy consumption, high pollution and high cost. The non-fired method for preparing fly ash ceramsite has the characteristics of low cost, low energy consumption and simple production process. The initial strength of the green ball is high and it is green and environmentally friendly. It has a broader development prospect and is in line with the national circular economy development concept. However, the strength and expansion coefficient of the non-fired ceramsite generated by the current non-fired ceramsite process technology are still inferior to those of sintered ceramsite, and the raw material cost is relatively high.
[0005] Therefore, the research and application of unfired expanded clay need to be further improved to improve the stability of product performance so as to better meet market needs. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of high energy consumption and high cost in the preparation of existing traditional ceramsite, as well as the problems of inferior strength and expansion coefficient of existing unfired ceramsite, and to provide a production process of fly ash type steam-cured ceramsite.
[0007] The technical solution of the present invention is as follows:
[0008] A production process of fly ash type steam-cured ceramsite, comprising the following steps:
[0009] (1) Take fly ash, silica fume, and diatomaceous earth as raw materials, add porogen and water according to the mass ratio, and preliminarily mix and pretreat for 30-50 minutes to obtain a pretreated material;
[0010] (2) adding cement and glucose to the material pretreated in step (1) and preliminarily mixing, placing in a granulator and mixing evenly to obtain a mixed raw material, and then adding a sodium hydroxide solution of 8% to 12% by mass of the mixed raw material;
[0011] (3) After the mixture is evenly mixed, an accelerating agent with a mass fraction of 10% to 15% of the mixed raw materials is added, and granulation is continued until completion;
[0012] (4) The granulated fly ash is naturally cured for 3-6 hours, and then steam-cured at 170-190° C. for 8-12 hours. After steam-curing, it is naturally cooled to room temperature to obtain fly ash steam-cured ceramsite.
[0013] Furthermore, the preparation method of the porogen in step (1) is as follows: 1-2 parts of sodium dodecylbenzene sulfonate, 0.1-0.5 parts of sodium methylene dinaphthalene sulfonate, 0.1-0.5 parts of fatty alcohol polyoxyethylene ether and 8-10 parts of water are mixed in weight proportions, heated to 40-50° C. and stirred for 5-10 minutes, then 0.2-0.3 parts of hydroxypropyl methylcellulose, 0.3-0.5 parts of calcium chloride and 1-2 parts of water are added under stirring, stirred for another 5-10 minutes, and cooled to room temperature to obtain the porogen.
[0014] Furthermore, in step (1), the mass ratio of fly ash, silica fume and diatomaceous earth is 8-10:1-2:1:2, the amount of porogen added is 1-2% of the mass of the raw materials, and the amount of water added is 10-20% of the mass of the raw materials.
[0015] Furthermore, the mass ratio of the pretreated material in step (2), cement and glucose is 8-10:2-3:0.01-0.02.
[0016] Furthermore, the concentration of the sodium hydroxide solution in step (2) is 5-6 mol / L.
[0017] Furthermore, the quick-setting agent in step (3) is composed of 30-40 parts of aluminum sulfate, 2-3 parts of diethanolamine, 4-5 parts of bentonite and 30-40 parts of water in terms of weight.
[0018] Furthermore, in step (2), the voltage of the granulator is controlled to be 380-420 V, the rotation speed of the stirring rod is 4-6 r / min, and the rotation speed of the material tray is 9-12 r / min.
[0019] Furthermore, in step (3), a gelling enhancer is added in an amount of 1% to 3% by mass of the mixed raw materials.
[0020] Furthermore, the gelling enhancer is glycerol.
[0021] Furthermore, the obtained ceramsite particle size ranges from 5 mm to 10 mm.
[0022] The beneficial effects of the present invention are:
[0023] (1) The technical solution disclosed in the present invention uses a combination of a porogen and an accelerator. The porogen is first used to foam the raw materials of fly ash, silica fume and diatomaceous earth. The evenly distributed tiny bubbles can relieve the expansion stress and osmotic pressure of the raw materials, and effectively solve the bulk density problem of expanded clay products. Cement and glucose are added to the pretreated raw materials for preliminary mixing. This process step can alleviate the problem of uneven material mixing caused by rapid coagulation of cement. Subsequently, the accelerator is used in coordination to effectively promote the increase of expanded clay strength.
[0024] (2) The present invention first regulates the ratio of raw materials. The fly ash accounts for more than 80% of the raw materials, which can effectively solve the problem of fly ash reuse. In addition, the expanded clay that meets the needs of construction can be prepared without high-temperature firing, which significantly reduces the production cost and energy consumption in the production process. The cylinder compressive strength of the obtained unfired expanded clay can effectively meet the needs of concrete pouring. It is not easy to fall off or crack during use, and has excellent durability.
[0025] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. DETAILED DESCRIPTION
[0026] The following describes the embodiments of the present invention through specific examples. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0027] The preparation method of the porogen used in the following examples is as follows: 2 parts of sodium dodecylbenzene sulfonate, 0.3 parts of sodium methylene dinaphthalene sulfonate, 0.2 parts of fatty alcohol polyoxyethylene ether (AEO-7) and 8 parts of water are mixed in weight proportions, heated to 45° C. and stirred for 10 minutes, then 0.2 parts of hydroxypropyl methylcellulose, 0.3 parts of calcium chloride and 1 part of water are added under stirring, and then stirred for 8 minutes. The porogen is obtained by cooling to room temperature.
[0028] Example 1
[0029] This embodiment prepares ceramsite according to the following steps:
[0030] (1) Take fly ash, silica fume, and diatomaceous earth as raw materials, add porogen and water according to the mass ratio, and pre-treat for 30-50 minutes by mixing. The mass ratio of fly ash, silica fume, and diatomaceous earth is 8:1:1. The amount of porogen added is 1% of the mass of the raw materials, and the amount of water added is 15% of the mass of the raw materials to obtain the pre-treated material;
[0031] (2) Cement (PO42.5R grade) and glucose are added to the material pretreated in step (1) for preliminary mixing, and the mixture is further mixed in a granulator to obtain a mixed material, and then a sodium hydroxide solution (5 mol / L) of 10% of the mass of the mixed raw materials is added; the mass ratio of the pretreated material, cement and glucose is 8:2:0.01; the voltage of the granulator is controlled to 420V, the speed of the stirring rod is 4r / min, and the speed of the feed plate is 9r / min.
[0032] (3) After mixing evenly, add 10% of the mass fraction of the mixture into an accelerating setting agent, and continue granulation until completion. The accelerating setting agent is composed of 30 parts of aluminum sulfate, 2 parts of diethanolamine, 4 parts of bentonite and 30 parts of water;
[0033] (4) The fly ash after granulation is naturally cured for 3 hours, and then steam-cured for 8 hours at 170°C under standard atmospheric pressure. After steam-curing, it is naturally cooled to room temperature to obtain fly ash ceramsite, and ceramsite with a particle size range of 5 mm to 10 mm is screened out.
[0034] Example 2
[0035] This embodiment prepares ceramsite according to the following steps:
[0036] (1) Take fly ash, silica fume, and diatomaceous earth as raw materials, add porogen and water according to the mass ratio, and pre-treat for 30-50 minutes. The mass ratio of fly ash, silica fume, and diatomaceous earth is 10:1:2, the amount of porogen added is 2% of the mass of the raw materials, and the amount of water added is 10% of the mass of the raw materials to obtain the pre-treated material;
[0037] (2) Cement (PO42.5R grade) and glucose were added to the material pretreated in step (1) for preliminary mixing, and the mixture was placed in a granulator for further mixing to obtain a mixed material, and then a sodium hydroxide solution (6 mol / L) accounting for 10% of the mass of the mixed material was added; the mass ratio of the pretreated material, cement and glucose was 10:3:0.02; the voltage of the granulator was controlled to 380 V, the speed of the stirring rod was 6 r / min, and the speed of the feed plate was 12 r / min.
[0038] (3) After mixing evenly, add 10% of the mass fraction of the mixture into an accelerating setting agent, and continue granulation until completion. The accelerating setting agent is composed of 40 parts of aluminum sulfate, 3 parts of diethanolamine, 5 parts of bentonite and 30 parts of water;
[0039] (4) The fly ash after granulation is naturally cured for 3 hours, and then steam-cured for 10 hours at 190° C. under standard atmospheric pressure. After steam-curing, it is naturally cooled to room temperature to obtain fly ash ceramsite, and ceramsite with a particle size range of 5 mm to 10 mm is screened out.
[0040] Example 3
[0041] This embodiment prepares ceramsite according to the following steps:
[0042] (1) Take fly ash, silica fume, and diatomaceous earth as raw materials, add porogen and water according to the mass ratio, and pre-treat for 30-50 minutes. The mass ratio of fly ash, silica fume, and diatomaceous earth is 8:1:2, the amount of porogen added is 1% of the mass of the raw materials, and the amount of water added is 20% of the mass of the raw materials to obtain the pre-treated material;
[0043] (2) Cement (PO42.5R grade) and glucose are added to the material pretreated in step (1) for preliminary mixing, and the mixture is placed in a granulator for further mixing to obtain a mixed raw material, and then a sodium hydroxide solution (5 mol / L) of 10% by mass of the mixed raw material is added; the mass ratio of the pretreated material, cement and glucose is 10:3:0.02; the voltage of the granulator is controlled to 380 V, the speed of the stirring rod is 6 r / min, and the speed of the feed plate is 12 r / min.
[0044] (3) After mixing evenly, add 10% of the mass fraction of the mixed material to accelerate the setting agent and 2% of the mass fraction of the mixed raw material to enhance the gelling agent glycerol, and continue granulation until completion. The accelerator is composed of 35 parts of aluminum sulfate, 2 parts of diethanolamine, 4 parts of bentonite and 35 parts of water;
[0045] (4) The granulated fly ash is naturally cured for 5 hours, and then steam-cured for 10 hours at 180° C. under standard atmospheric pressure. After steam-curing, the fly ash ceramsite is naturally cooled to room temperature to obtain fly ash ceramsite, and ceramsite with a particle size range of 5 mm to 10 mm is screened out.
[0046] Comparative Example 1
[0047] A method for preparing sintered ceramsite comprises the following steps:
[0048] (1) Take fly ash, silica fume, and diatomaceous earth as raw materials, add porogen and water according to the mass ratio, the mass ratio of fly ash, silica fume, and diatomaceous earth is 8:1:1, the amount of porogen added is 1% of the mass of the raw materials, and the amount of water added is 15% of the mass of the raw materials;
[0049] (2) Add cement to the raw materials of step (1) and mix them uniformly, and then put them into a granulator for further mixing. The mass ratio of raw materials to cement is 8:2:0.01. The voltage of the granulator is controlled to 420V, the speed of the stirring rod is 4r / min, and the speed of the material plate is 9r / min to prepare raw material balls.
[0050] (3) The raw material balls were placed in a drying oven and dried at 80°C for 10 h. The dried raw material balls were placed in a box-type resistance furnace and pre-burned at 500°C for 20 min. The temperature was then raised to 1050°C and calcined for 20 min at a heating rate of 3°C / min.
[0051] Comparative Example 2
[0052] The difference from Example 1 is that step (1) does not use a porogen, and the other process steps remain the same as Example 1.
[0053] Comparative Example 3
[0054] The difference from Example 1 is that the porogen used in step (1) is a commercially available foaming agent purchased from Jinan Xinlongsheng Biotechnology Co., Ltd. (sodium lignin sulfonate), and the other process steps are consistent with Example 1.
[0055] Comparative Example 4
[0056] The difference from Example 1 is that glucose and accelerating setting agent are not used in step (2), and the other process steps are consistent with Example 1.
[0057] The cylinder pressure strength and bulk density of the ceramsite obtained in the above embodiments and comparative examples were tested, and the heavy metal leaching test of sludge incineration ash and ceramsite was carried out using the national standard HJ557-2009 "Solid Waste Leaching Toxicity Leaching Method Horizontal Oscillation Method", and the concentration of heavy metal elements such as Cu, Cd, As, Cr, Ni, and Pb in the filtrate was detected using an inductively coupled plasma atomic emission spectrometer. The results are shown in Table 1.
[0058] Table 1 Test results
[0059]
[0060]
[0061] It can be seen from Table 1 that the cylinder pressure strength of the unburned ceramsite obtained in the embodiment is close to the sintered ceramsite in Comparative Example 1. The unburned ceramsite of the present invention does not need to be sintered, has low manufacturing cost, and is environmentally friendly. At the same time, compared with the existing unburned ceramsite, the unburned ceramsite of the present invention has good performance, higher cylinder pressure strength, and excellent durability. And through the heavy metal toxicity leaching detection, it can be shown that the heavy metal element content detected by the unburned ceramsite prepared by the technical solution of the present invention is far lower than the national limit standard for hazardous waste, indicating that the preparation of the unburned ceramsite has a good fixing effect on the heavy metals in the raw materials.
[0062] And from Comparative Examples 2-4, it can be further reflected that the pore-forming agent of the present invention has a significant effect on improving the bulk density of ceramsite, and the effect is obviously better than that of commercially available foaming agents. The combination of glucose and accelerator has the best effect on optimizing the strength and expansion coefficient of the product ceramsite.
[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A production process of fly ash type steam-cured ceramsite, characterized in that: The steps include: (1) Take fly ash, silica fume, and diatomaceous earth raw materials, add porogen and water according to the mass ratio, and preliminarily mix and pretreat for 30-50 minutes to obtain the pretreated material; (2) adding cement and glucose to the material pretreated in step (1) and preliminarily mixing, placing in a granulator and mixing evenly to obtain a mixed raw material, and then adding a sodium hydroxide solution of 8% to 12% by mass of the mixed raw material; (3) After the mixture is evenly mixed, an accelerating agent with a mass fraction of 10% to 15% of the mixed raw materials is added, and granulation is continued until completion; (4) The granulated fly ash is naturally cured for 3-6 hours, and then steam-cured at 170-190° C. for 8-12 hours. After steam-curing, it is naturally cooled to room temperature to obtain fly ash steam-cured ceramsite.
2. The production process of fly ash type steam-cured ceramsite according to claim 1, characterized in that: The preparation method of the porogen in step (1) is as follows: 1-2 parts of sodium dodecylbenzene sulfonate, 0.1-0.5 parts of sodium methylene dinaphthalene sulfonate, 0.1-0.5 parts of fatty alcohol polyoxyethylene ether and 8-10 parts of water are mixed in weight proportions, heated to 40-50° C. and stirred for 5-10 minutes, then 0.2-0.3 parts of hydroxypropyl methylcellulose, 0.3-0.5 parts of calcium chloride and 1-2 parts of water are added under stirring conditions, stirred for another 5-10 minutes, and cooled to room temperature to obtain the porogen.
3. The production process of fly ash type steam-cured ceramsite according to claim 1, characterized in that: Step (1) The mass ratio of fly ash, silica fume and diatomaceous earth is 8-10:1-2:1:2, the amount of porogen added is 1-2% of the mass of the raw materials, and the amount of water added is 10-20% of the mass of the raw materials.
4. The production process of fly ash steam-cured ceramsite according to claim 1, characterized in that: The mass ratio of the pretreated material in step (2), cement and glucose is 8-10:2-3:0.01-0.
02.
5. The production process of fly ash steam-cured ceramsite according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step (2) is 5-6 mol / L.
6. The production process of fly ash type steam-cured ceramsite according to claim 1, characterized in that The quick-setting agent in step (3) is composed of 30-40 parts of aluminum sulfate, 2-3 parts of diethanolamine, 4-5 parts of bentonite and 30-40 parts of water in terms of mass.
7. The production process of fly ash type steam-cured ceramsite according to claim 1, characterized in that: In step (2), the voltage of the granulator is controlled to be 380-420 V, the rotation speed of the stirring rod is 4-6 r / min, and the rotation speed of the feed plate is 9-12 r / min.
8. The production process of fly ash type steam-cured ceramsite according to claim 1, characterized in that: Furthermore, in step (3), a gelling enhancer is added in an amount of 1% to 3% by mass of the mixed raw materials.
9. The production process of fly ash type steam-cured ceramsite according to claim 8, characterized in that: The gelling enhancer is glycerol.
10. The production process of fly ash type steam-cured ceramsite according to claim 1, characterized in that: The obtained ceramsite particle size ranges from 5mm to 10mm.